2020
DOI: 10.1021/acsomega.0c03584
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Efficacy of Environmentally Benign Silver Nanospheres for Organic Transformation, Photocatalysis, and Water Remediation

Abstract: Highly crystalline and monophasic silver nanospheres with a high specific surface area of 57 m 2 /g have been synthesized by an environmentally benign rapid chemical reduction using l -alanine for catalytic transformation, photocatalytic degradation, and bacterial disinfection, which can provide an ample strategy for water remediation. Electron microscopic analysis confirms the spherical morphology of as-prepared silver nanoparticles with an average grain size of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The SPR of the metal nanoparticles depends on the shape, size, and surrounding dielectric medium, as SPR is the resonant oscillation of conduction electrons under appropriate light illumination [ 12 , 13 , 14 ]. Silver nanoparticles are well-known noble metallic materials with strong antimicrobial and photocatalytic properties because of their high sensitivity, chemical stability, and better light absorption and optical properties [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SPR of the metal nanoparticles depends on the shape, size, and surrounding dielectric medium, as SPR is the resonant oscillation of conduction electrons under appropriate light illumination [ 12 , 13 , 14 ]. Silver nanoparticles are well-known noble metallic materials with strong antimicrobial and photocatalytic properties because of their high sensitivity, chemical stability, and better light absorption and optical properties [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their accumulation has been increased due to increased industrial operations, technological progress, and ineffective preventive measures [ 2 ]. The carcinogenic nature of dyes, low biodegradability, and half-life of more than 2000 hours under sunlight irradiation have urged researchers to invent a constant solution [ 3 ]. Therefore, a lot of research work has been reported to develop effective environmental remediation technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The as-measured reflectance data were converted to F ( R ∞ ) employing the Kubelka–Munk equation, where the function F ( R ∞ ) = (1 − R ∞ ) 2 /2 R ∞ was considered as absorbance and used for the optical band determination as reported elsewhere. 12 Fig. 6d presents the plots, where the x -axis represents energy and the y -axis belongs to the [ F ( R ∞ ) hν ] 1/ n of the 1%, 2.5%, and 5% Ag–SnO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Many attempts have been made for the reduction of 4-NP using a suitable catalyst. 12–15 To solve these environmental crises, an effective strategy is to employ semiconductor-mediated photocatalysis. 16,17 Metal oxide semiconductors possess a low price, environmental friendliness, recyclability, abundant accessibility, and excellent degradation proficiency.…”
Section: Introductionmentioning
confidence: 99%